Pengembangan Sistem Self Ordering Mimi Cakes and Cookies Berbasis Web Dengan Metode Rapid Application Development (RAD) - Herdiansah, Arief; Ramadhani, Ryan Zulham; Mahpud, Mahpud; Frithadila, Najmah (LPPM Universitas Bina Sarana Informatika, 2024)
The food order recording system can cause errors in recording orders, lose data and require a lot of time in the process of recording and reporting orders. Product marketing carried out using social media requires sellers to upload product photos one by one so that buyers can see them. This is more troublesome if the ordering process is carried out conventionally. This research is applied research on the development of a food ordering information system with a self-ordering concept which can be an alternative solution to replace conventional food ordering systems. This research was conducted at Mimi Cakes & Cookies MSME, which currently still uses conventional methods in the process of recording pre-orders for the food it sells. This research uses the Rapid Application Development (RAD) development method. The system was developed using the PHP Framework Codelgniter programming language with the VS Code text editor. The system development results were tested using the black box testing method. The results of this research produce a pre-order system with a Web-based self-ordering concept that can provide a solution to the problem of recording and reporting orders for Mimi Cakes & Cookies MSMEs. The system developed has also caused the number of orders for Mimi Cakes and Cookies to increase by 20%